Analisis Potensi Demand LRT Bandara Soekarno-Hatta – Kemayoran Pada Sektor Transportasi Jabodetabek Dengan Pendekatan Sistem Dinamis - Ellenlies, Ellenlies; Suryobuwono, Abdullah Ade; Mahersa, Raka Putra (Institut Transportasi dan Logistik Trisakti, 2022)
This thesis discusses the analysis of potential demand to find out how much people's interest and preference for a transportation development. Jabodetabek is an area that has the busiest transportation activities and of course it is not free from traffic jams. Therefore, a suitable public transportation mode for urban areas is needed, one of which is LRT. The use of dynamic system theory as a basis to find out how much demand people. The transportation mode analyzed is LRT, especially on the Soekarno-Hatta - Kemayoran route. The results of this study indicate that demand is publicvery high for the LRT Soekarno-Hatta Airport - Kemayoran.